2018
DOI: 10.1088/1361-6528/aabbd0
|View full text |Cite
|
Sign up to set email alerts
|

VSION as high field MRI T1 contrast agent: evidence of their potential as positive contrast agent for magnetic resonance angiography

Abstract: Because of their outstanding magnetic properties, iron oxide nanoparticles have already been the subject of numerous studies in the biomedical field, in particular as a negative contrast agent for T-weighted nuclear magnetic resonance imaging, or as therapeutic agents in hyperthermia experiments. Recent studies have shown that below a given particle size (i.e. 5 nm), iron oxide may be used to provide a significant positive (brightening) effect on T-weighted MRI. In such an application, not only the size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Results showed that IONPs with a thinner coating yielded an excellent positive T 1 -MRI contrast, more specifically NPs synthesised at 120 • C. These NPs, with a hydrodynamic size of 7.9 nm and a r 2 /r 1 ratio of 1.9 showed great contrast enhancement in both body and brain MRA of healthy mice, providing the possibility of better visualising their vasculature. In 2018, Vangijzegem et al [98] synthesised very small PEGylated iron oxide nanoparticles (VSIONPs) with core sizes of 3.5 nm that showed positive contrast in in vivo MRA, enabling the heart chamber and the vena cava of healthy mice to be observed.…”
Section: Iron-based and Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Results showed that IONPs with a thinner coating yielded an excellent positive T 1 -MRI contrast, more specifically NPs synthesised at 120 • C. These NPs, with a hydrodynamic size of 7.9 nm and a r 2 /r 1 ratio of 1.9 showed great contrast enhancement in both body and brain MRA of healthy mice, providing the possibility of better visualising their vasculature. In 2018, Vangijzegem et al [98] synthesised very small PEGylated iron oxide nanoparticles (VSIONPs) with core sizes of 3.5 nm that showed positive contrast in in vivo MRA, enabling the heart chamber and the vena cava of healthy mice to be observed.…”
Section: Iron-based and Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Both procedures allow the formation of nearly monodisperse iron oxide nanoparticles, with tunable sizes, by simply varying the experimental parameters based on the precise separation between the nucleation and the growth steps involved in the formation mechanism of the nanocrystals [35]. For the preparation of VSION, we decided to apply a previously established process [20] which consisted in the direct injection of a solution containing the iron organometallic complex solubilized in oleylalcohol in a solution of hydrophobic surfactants (e.g., oleic acid, oleylamine and 1,2-hexadecanediol in a 1:1:5 molar ratio) in a dibenzylether solution preheated at 300 • C. As a result, VSION with well-defined properties were readily obtained. Figure 1A presents a TEM image of the resulting nanoparticles which show spherical morphology and exhibiting an average diameter of 3.5 ± 0.6 nm (PDI: 1.1).…”
Section: Vsion Formation By Thermal Decomposition Using Batch Processmentioning
confidence: 99%
“…Nanomaterials 2020, 10, x FOR PEER REVIEW 5 of 18 growth steps involved in the formation mechanism of the nanocrystals [35]. For the preparation of VSION, we decided to apply a previously established process [20] which consisted in the direct injection of a solution containing the iron organometallic complex solubilized in oleylalcohol in a solution of hydrophobic surfactants (e.g., oleic acid, oleylamine and 1,2-hexadecanediol in a 1:1:5 molar ratio) in a dibenzylether solution preheated at 300 °C. As a result, VSION with well-defined properties were readily obtained.…”
Section: Vsion Formation By Thermal Decomposition Using Batch Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, MPO(Gd) is sensitive to myeloperoxidase enzymes that is beneficial for detection of vulnerable plaques. However, due to the increased possibility of nephrotoxicity of gadolinium‐based contrast agents, ION‐based positive contrast agents have become a research hotspot today …”
Section: Applicationsmentioning
confidence: 99%